Operational and organisational stressors in community correctional work: Insights from probation and parole officers in Ontario, Canada - Norman, Mark (Probation journal, 2022)
In the current article, we investigate the occupational stressors parole and probation officers working in provincial correctional services in Ontario, Canada experience. We examine four specific stressors that emerged thematically from participants’ open-ended survey responses, and conceptualize these as operational factors (i.e., the duties of the job) or organisational factors (i.e., structural aspects of the organisation in which parole or probation officers work). Participants identified the operational stressor of exposure to potentially psychologically traumatic events and secondary trauma, as well as three predominant organisational stressors: paperwork and administrative tasks, insufficient human resources, and workplace relationships and tensions. Drawing from literatures on parole and probation, workplace stress, and organisational cultures and behaviours, we analyse how these stressors have detrimental impacts on the mental health and well-being of community correctional workers, which in turn compromises their ability to effectively supervise and support individuals on their caseload. Policy and well-being implications are discussed.